Understanding the “Marmeleiros”: a taxonomic treatment of Croton sect. Lasiogyne (Euphorbiaceae) in Brazil - Rossine, Yuri; de Melo, André Laurênio; Athiê-Souza, Sarah Maria; de Sales, Margareth Ferreira (Phytotaxa, 2023)
We present here a taxonomic treatment of Croton sect. Lasiogyne occurring in Brazil. This study is based on field collections and analyses of more than 1,300 specimens held in 47 herbaria. Eleven species are recorded in Brazil, occurring in almost all phytogeographic domains (except the Pampa). Six species of those species are endemic to that country (Croton blanchetianus, C. claussenianus, C. compressus, C. jacobinensis, C. limae, and C. suassunae). The total absence of extrafloral nectaries and reduplicate-valvate sepals, or valvate sepals, are proposed here as morphological characteristics for the recognition of Brazilian species of the section Lasiogyne. The main characters used to differentiate the species are: branching pattern, stipule shape, venation, trichome type, shape of the sepals of the pistillate flower, shape and number of ramifications of the style, capsule shape, and seed surface texture. Croton macrocalyx is excluded here from this section and positioned in C. sect. Barhamia.